Antiferromagnetic ordering in van der Waals 2D magnetic material MnPS3 probed by Raman spectroscopy - Kim, Kangwon; Lim, Soo Yeon; Kim, Jungcheol; Lee, Jae Ung; Lee, Sungmin; Kim, Pilkwang; Park, Kisoo; Son, Suhan; Park, Cheol Hwan; Park, Je Geun; Cheong, Hyeonsik (2D Materials, 2019)
Magnetic ordering in the two-dimensional (2D) limit has been one of the most important issues in condensed matter physics for the past few decades. The recent discovery of new magnetic van der Waals materials heralds a much-needed easy route for the studies of 2D magnetism: the thickness dependence of the magnetic ordering has been examined using Ising- and XXZ-type magnetic van der Waals materials. Here, we investigated the magnetic ordering of MnPS3, a 2D antiferromagnetic material of the Heisenberg-type, by Raman spectroscopy from bulk all the way down to the bilayer. The phonon modes that involve the vibrations of Mn ions exhibit characteristic changes as the temperature gets lowered through the Néel temperature. In bulk MnPS3, the Raman peak at ∼155 cm-1 becomes considerably broadened near the Néel temperature, and upon further cooling is subsequently red-shifted. The measured peak positions and polarization dependences of the Raman spectra are in excellent agreement with our first-principles calculations. In few-layer MnPS3, the peak at ∼155 cm-1 exhibits the characteristic red-shift at low temperatures down to the bilayer, indicating that the magnetic ordering is surprisingly stable at such a thin limit. Our work sheds light on the hitherto unexplored magnetic ordering in the Heisenberg-type antiferromagnetic systems in the atomic-layer limit.
Keywords: Antiferromagnetic orderings; Antiferromagnetic systems; First-principles calculation; Isotropic Heisenberg; MnPS3; Polarization dependence; Thickness dependence; Two Dimensional (2 D); antiferromagnetism; isotropic Heisenberg model; magnetic ordering; manganese phosphorus trisulfide; MnPS3; Raman spectroscopy